SOCIAL ECONOMIC LAW AND PUBLIC POLICY INNOVATION: AN ANALYSIS OF RECENT LITERATURE - Loso Judijanto; Mohd Syahrin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The integral relationship between social economy law and public policy innovation, two disciplines that are increasingly relevant in the face of contemporary economic and social challenges. Recent literature shows that combining the principles of social economy law with innovations in public policy making can lead to more effective, inclusive, and adaptive approaches. Social economic law offers a normative framework orientated towards social justice while maintaining economic stability, while public policy innovation introduces creative and participatory methods that allow policies to be more responsive to changing social dynamics. This combination is identified as an effective way to develop evidence- based policies that prioritise sustainability and inclusiveness, and are able to address future challenges with a holistic approach.